Pengaruh Pemberian Virgin Coconut Oil Terhadap Kadar TNF- dan Jumlah Leukosit Pada Tikus Putih Jantan (Rattus norvegicus) Model Hiperkolesterolemia - Mutmainnah; Ichwan Baihaki (Universitas Mohammad Husni Thamrin, 2025)
Hypercholesterolemia contributes to oxidative stress, which may cause dysregulation of the proinflammatory response as indicated by increased levels of TNF-α and leukocyte count, both of which are risk factors for metabolic syndrome. Exogenous antioxidants such as tocopherol are required to interrupt the chain reactions of free radicals, while lauric acid functions as an anti-inflammatory agent that enhances immunity. These compounds are contained in virgin coconut oil (VCO). Aimed to determine the effect of VCO administration on the reduction of total cholesterol levels, TNF-α concentrations, and leukocyte counts. This experimental study employed a post-test only control group design. Twenty-four male Wistar rats were randomly divided into four groups. Group K0 received neither a high-cholesterol diet nor VCO. Group K1 received a high-cholesterol diet without VCO. Groups P1 and P2 received a high-cholesterol diet along with VCO at doses of 0.9 mL/200 g BW/day and 0.45 mL/200 g BW/day, respectively. On day 21, blood samples were collected to measure total cholesterol, TNF-α, and leukocyte count at the PSPG UGM Laboratory. The One-way ANOVA showed significant differences in TNF-α and leukocyte counts among groups (p=0.000). Post hoc Tamhane’s and Tukey tests demonstrated that TNF-α and leukocyte levels in groups K0, P1, and P2 differed significantly from those in K1 (p<0.05). Administration of virgin coconut oil effectively reduced TNF-α, and leukocyte count levels. Keywords: Leukocyte counts, TNF-α, VCO